PERANCANGAN ULANG INTERIOR STASIUN KERETA API PEKALONGAN DENGAN PENDEKTAN BEHAVIOR REDESIGN OF PEKALONGAN RAILWAY STATION INTERIOR WITH BEHAVIOR APPROACH - Agustriani, Marina; Liritantri, Widyanesti; Puspa Nabila, Ganesha (Telkom University, 2024)
This design aims to bring about significant changes to Pekalongan RailwayStation, focusing on the theme